Donor–acceptor conjugated polymers based on two-dimensional thiophene derivatives for bulk heterojunction solar cells. Issue 2 (25th November 2016) - Dong, Xin; Tian, Hongkun; Xie, Zhiyuan; Geng, Yanhou; Wang, Fosong
Abstract : D–A conjugated polymers based on accessible 2D conjugated ( E )-1, 2-bis(5-alkyl-[2, 3′-bithiophen]-2′-yl)ethene units possess low bandgaps, shorter π–π stacking distances, higher mobility and higher photovoltaic performance. Abstract : Four donor–acceptor (D–A) conjugated polymers (CPs), i.e., poly[( E )-1, 2-bis(5-(2-hexyldecyl)-[2, 3′-bithiophen]-2′-yl)ethene- alt -5, 6-difluorobenzo[ c ][1, 2, 5]thiadiazole] (PTVT-T8 ), poly[( E )-1, 2-bis(5-(2-octyldodecyl)-[2, 3′-bithiophen]-2′-yl)ethene- alt -5, 6-difluorobenzo[ c ][1, 2, 5]thiadiazole] (PTVT-T10 ), poly[( E )-1, 2-bis(3-(2-hexyldecyl)thiophen-2-yl)ethene- alt -5, 6-difluorobenzo[ c ][1, 2, 5]thiadiazole] (PTVT-C8 ) and poly[( E )-1, 2-bis(3-(2-octyldodecyl)thiophen-2-yl)ethene- alt -5, 6-difluorobenzo[ c ][1, 2, 5]thiadiazole] (PTVT-C10 ) were synthesized and characterized. Compared toPTVT-C8 andPTVT-C10, PTVT-T8 andPTVT-T10 that comprise two-dimensional (2D) conjugated D units displayed lower bandgaps, more rigid backbones, higher self-organization ability and shorter π–π stacking distances (∼3.5 Å). As a result, the hole mobility ofPTVT-T8 andPTVT-T10 (up to 0.42 cm 2 (V s) −1 ) was one magnitude higher than that ofPTVT-C8 andPTVT-C10 (up to 0.039 cm 2 (V s) −1 ), as measured with organic field-effect transistors (OFETs). Polymer solar cells (PSCs) of these polymers were prepared with PC71 BM as an acceptor and o -xylene as a processing solvent, and power conversion efficiencies (PCEs) up to 6.79%, 5.65%, 3.94% and 1.70% were achieved forPTVT-T8, PTVT-T10, PTVT-C8 andPTVT-C10, respectively.PTVT-T8 andPTVT-T10 exhibited photovoltaic properties superior toPTVT-C8 andPTVT-C10 owing to their high hole-mobility and the formation of ordered nano-fibrillar structures in which polymer backbones preferred face-on arrangement.